Formulasi Hair Tonic Berbahan Dasar Daun Teh (Camellia sinensis) sebagai Stimulasi Pertumbuhan Rambut - Cut Suraiya Wahyuni Utami (Pusat Riset dan Inovasi Nasional, 2025)
The stability and dosage test of tea leaf ethanol extract hair tonic (Camellia sinensis) was conducted with the aim of spreading stability, which includes organoleptic aspects (shape, color, and aroma), homogeneity, and pH, as well as to assess hair growth activity. The extract was obtained using the maceration method and solidified using a rotary evaporator. This study was divided into three groups, namely the positive control group (Johnny Andrean hair tonic), negative control (base hair tonic preparation), and hair tonic extract (HTE). The resulting HTE preparation was a clear, blackish brown solution with a distinctive menthol aroma. Accelerated stability testing was carried out using the cycling test method for 12 days, and the results showed changes in the preparation, namely the solution becoming slightly cloudy and inhomogeneous. The results of the hair growth activity test for 28 days, the hair was pulled out using tweezers then straightened and attached to tape, then measured using a caliper, showed an increase in average hair length every week in all groups. The average value of hair length given HTE was higher than the positive and negative controls. LSD statistical test on mean hair length showed significant differences between positive control, negative control, and HTE.